UPAYA MENINGKATKAN KEMAMPUAN BERHITUNG SISWA SD/MI MELALUI PELATIHAN CARA CEPAT DAN TEPAT BERHITUNG DI DESA PRINGGACALA KECAMATAN KARANGAMPEL - Denni Ismunandar; Dian Rohaeni; Feramawati Feramawati (universitas wiralodra, 2019)
Training is one element in creating more qualified individuals. Training is very necessary in the learning process so that students are not bored with monotone learning when in class. Therefore, it is necessary to hold a training for students on how to quickly and accurately count to make it easier for students to calculate addition and multiplication operations. With this activity students are expected to be able to more easily understand the material in mathematics. In addition, students are also expected to be motivated to study harder and not think that mathematics is difficult. From the results of the activity, it was obtained input that students desperately need training in a quick and precise way of counting to make it easier for students to calculate addition, subtraction and multiplication. The impact is that student learning outcomes can be better and students prefer mathematics subjects. Participants expect that this community service activity can be carried out as often as possible and continuously so that communication between schools and universities is maintained in the development of learning.